Exogenous dopamine application ameliorates chilling injury and preserves quality of kiwifruit during cold storage - Morteza Soleimani Aghdam; Zeinab Asle-Mohammadi; Amin Ebrahimi; Farhang Razavi (Scientific Reports)
Abstract This study investigated the mechanisms employed by exogenous dopamine application in alleviating chilling injury in kiwifruits during storage at 1 °C for 120 days. Our results indicated that dopamine treatment at 150 µM alleviated chilling injury in kiwifruits during storage at 1 °C for 120 days. By 150 µM dopamine application, higher SUMO E3 ligase (SIZ1) and target of rapamycin (TOR) genes expression accompanied by lower poly(ADP-Ribose) polymerase 1 (PARP1) and sucrose non-fermenting 1-related kinase 1 (SnRK1) genes expression was associated with higher salicylic acid, ATP, NADPH and proline accumulation in kiwifruits during storage at 1 °C for 120 days. In addition, higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity arising from higher phenols and flavonoids accumulation in kiwifruits treated with 150 µM dopamine could be ascribed to higher phenylalanine ammonia-lyase (PAL) enzyme activity. Additionally, lower endogenous hydrogen peroxide (H2O2) accumulation along with higher ascorbic acid accumulation in kiwifruits treated with 150 µM dopamine could be attributed to lower superoxide dismutase (SOD) along with higher catalase (CAT) enzymes activity. Moreover, lower phospholipase D (PLD) and lipoxygenase (LOX) genes expression in kiwifruits treated with 150 µM dopamine was accompanied with membrane integrity preservation as evidenced by lower electrolyte leakage and malondialdehyde (MDA) accumulation. Therefore, exogenous dopamine could be employed as a potential technique for alleviating chilling injury in kiwifruits during cold storage.